2-[(4-Phenylpiperazin-1-yl)methyl]imidazo(di)azines as Selective D4-Ligands. Induction of Penile Erection by 2-[4-(2-Methoxyphenyl)piperazin-1-ylmethyl]imidazo[1,2-a]pyridine (PIP3EA), a Potent and Selective D4 Partial Agonist - Gmeiner, Peter; Hübner, Harald; et al. (Journal of Medicinal Chemistry, 2006)
A series of novel 2-[(4-phenylpiperazin-1-yl)methyl]imidazoazines and aza-analogues were prepared and screened at selected dopamine, serotonin, and adrenergic receptor subtypes. 2-Substituted imidazopyridines and pyridazines presented high affinities and selectivities for D4 dopamine receptors. Whereas functional experiments indicated neutral antagonists or weak partial agonist effects for most of the target compounds, the 2-methoxyphenyl substituted 2-piperazinylmethylimidazopyridine 3c (PIP3EA) displayed substantial agonist efficacy in mitogenesis experiments and GTPγS binding tests, resulting in EC50 values of 3.0 (46%) and 4.5 nM (57%), respectively. Our D4 agonist 3c induced penile erection in vivo when administered to rats. This effect was inhibited by L-745,870 a D4 selective antagonist, confirming the mechanistic pathway. © 2006 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.lphch.24phen